Simulation of Chloride Diffusion in Concrete Based on a New Mesoscopic Numerical Method - Ling Yao; Lixia Ren; Guoli Gong; Jianqiang Zhang (Advances in Civil Engineering)
Chloride diffusion-induced corrosion is a major factor that affects the durability of concrete structures. Thus, the study of chloride diffusion in concrete is important. In this study, a mesoscopic structure model is proposed and used to investigate chloride diffusion in concrete. The concrete is assumed to be a heterogeneous material composed of two phases of aggregate and mortar matrix. The aggregates are randomly distributed convex polygons. The chloride diffusion is assumed to occur only in the mortar matrix phase. The modified chloride diffusion coefficient in the mesoscale model is proposed. The effect of a single aggregate in chloride diffusion in concrete is analyzed. The present numerical model is validated on the basis of the experimental data. The influence of aggregate in the presented model, including aggregate random distribution form, aggregate content, and the validity of polygonal aggregate based on circle, is explored further. The simulation results indicate that the polygonal aggregate random distribution has a negligible influence on chloride diffusion in concrete, the polygonal aggregate content has a certain effect, and the presented mesoscale numerical model is an effect method for predicting the chloride diffusion in concrete.